2003
DOI: 10.1007/s00248-002-0107-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotaxis of Cyanobacteria in Desert Crusts

Abstract: We studied the migration of cyanobacteria in desert crusts from Las Bárdenas Reales (Spain). The crusts were almost exclusively colonized by the filamentous cyanobacterium Oscillatoria, which formed a dense layer approximately 600 lm thick located between 1.5 and 2.1 mm deep. Laboratory and field experiments showed that saturation of the crust with liquid water induced a migration of the cyanobacteria leading to a significant greening of the surface within a few minutes. Under light and rapid evaporation, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 26 publications
(43 reference statements)
2
46
1
Order By: Relevance
“…Spectral field radiance measurements of downwelling or backscattered light can be used to describe the zonation and migration of differently pigmented photosynthetic microbes at high spatial resolution (e.g., Jørgensen and Des Marais, 1986;Kü hl et al, 1994a;Bebout and GarciaPichel, 1995;Pringault and Garcia-Pichel, 2004) and have also been used to study the microscale distribution of special protective host pigments in symbiont-bearing corals (Salih et al, 2000); such measurements complement similar studies based on microscale fluorescence measurements with tapered microprobes (see later). However, it is important to realize that FIG.…”
Section: Fiber-optic Microprobes For Mapping Light Fieldsmentioning
confidence: 83%
“…Spectral field radiance measurements of downwelling or backscattered light can be used to describe the zonation and migration of differently pigmented photosynthetic microbes at high spatial resolution (e.g., Jørgensen and Des Marais, 1986;Kü hl et al, 1994a;Bebout and GarciaPichel, 1995;Pringault and Garcia-Pichel, 2004) and have also been used to study the microscale distribution of special protective host pigments in symbiont-bearing corals (Salih et al, 2000); such measurements complement similar studies based on microscale fluorescence measurements with tapered microprobes (see later). However, it is important to realize that FIG.…”
Section: Fiber-optic Microprobes For Mapping Light Fieldsmentioning
confidence: 83%
“…They also remain mostly inactive in these desiccated environments, but after a few minutes under moisture they were able to activate photosynthesis and respiration (Garcia-Pichel and Pringault, 2001;Pringault and Garcia-Pichel, 2004). These authors repeatedly tested migration with or without light and without chemical variations, and concluded that the migration response was caused by the water effect.…”
Section: Discussionmentioning
confidence: 99%
“…Migration can represent an adaptive mechanism for microorganisms to respond to adverse conditions -e.g. UV radiations (Bebout and Garcia-Pichel, 1995) or desiccation (Pringault and Garcia-Pichel, 2004). Vertical migration of phototrophic primary producers within the mat has important consequences on the rates of photosynthesis (Bebout and Garcia-Pichel, 1995), and potentially on the oxygen consumption depending on the strength of the coupling between primary producers and the heterotrophic bacteria (see 4.2).…”
Section: The Role Of Migration In the Metabolic Changes Observedmentioning
confidence: 98%